Genetic variability and divergence studies in mungbean (Vigna radiata) under rainfed conditions - KUMAR, SANJEEV; KUMAR, ANIL; ABROL, VIKAS; SINGH, A P; SINGH, ANJANI KUMAR (The Indian Journal of Agricultural Sciences, 2020)
Twenty three genotypes of moongbean were evaluated in two different environments for variability stability performance. The present investigation was conducted to provide information on the nature and magnitude of genetic variability and divergence among 23 genotypes of mungbean under different environments. It was measured by seed yield/plant under rainfed conditions during kharif 2016 and 2017. Seed yield/plant showed significant correlation with number of seeds/pod and negative correlation with days to maturity. These genotypes were divided into five clusters on the basis of D2 statistics. Maximum inter cluster distance was exhibited by cluster IV and intra-cluster distance by cluster I. Hence, the genotypes of cluster III & IV shall be utilized for the hybridization programme for the development of high yielding varieties (HYVs) of mungbean.